2023
DOI: 10.3389/fpsyg.2023.1183084
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions for healthcare workers at a Swedish university hospital infectious disease department during the COVID-19 pandemic: barriers and facilitators to maintaining employee wellbeing

Abstract: BackgroundHealthcare workers (HCWs) at infectious disease departments have held the frontline during the COVID-19 pandemic. This study aimed to identify barriers and facilitators to maintaining the employees’ wellbeing that may be used to increase preparedness for future pandemics within ID Departments.MethodsIn September 2020, a web-based survey on demographics and work environment was distributed to all HCWs at the Infectious Disease Department at Sahlgrenska University Hospital. Results were compared with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Several studies have previously shown that work-related stress is closely connected to mental health issues among healthcare professionals (e.g., Björk et al 2023;Gadolin et al 2022;Kim et al 2018;Rodriguez-Vega et al 2022;Veje et al 2023). A study by Zhou et al (2020) showed that because of the pandemic, healthcare staff had a higher risk of developing mental health problems due to a higher workload than before the pandemic.…”
Section: Mental Health Issues Among Healthcare Professionalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have previously shown that work-related stress is closely connected to mental health issues among healthcare professionals (e.g., Björk et al 2023;Gadolin et al 2022;Kim et al 2018;Rodriguez-Vega et al 2022;Veje et al 2023). A study by Zhou et al (2020) showed that because of the pandemic, healthcare staff had a higher risk of developing mental health problems due to a higher workload than before the pandemic.…”
Section: Mental Health Issues Among Healthcare Professionalsmentioning
confidence: 99%
“…An additional aspect was the importance of collaboration between the crisis managers and other managers, among other things as a way of identifying members of staff in need of additional support and treatment to avoid developing chronic issues. Previous studies have shown increased mental health issues among healthcare professionals during the pandemic (e.g., Björk et al 2023;Veje et al 2023;Zhang et al 2020;Zhou et al 2020). A study by Malik et al (2021) described how vulnerable members of staff were identified precisely in collaboration with their managers to be able to offer them extra support.…”
Section: External Focus Areasmentioning
confidence: 99%